Efektivitas PGPR dan Nanosilika terhadap Pertumbuhan dan Hasil Kedelai Varietas Anjasmoro di Tanah Regosol - Umami, Arif; Wiharyanti, Risma (Jurnal Agro Wiralodra, 2025)
Soybean production in Indonesia currently does not meet national demand. However, there is potential to increase production by utilizing sub-optimal lands, such as Regosol soils. Regosol soils are characterized by a high sand content, low fertility, and poor water-holding capacity, which exposes plants to drought stress. To enhance soybean productivity under such conditions, technological innovations are needed, including the use of biofertilizers and nanotechnology. The Anjasmoro soybean variety is known to be relatively sensitive to drought stress. The application of Plant Growth-Promoting Rhizobacteria (PGPR) and nanosilica is expected to improve nutrient uptake, stimulate the production of growth-promoting hormones, and enhance plant tolerance to drought stress. This study aimed to evaluate the growth and yield of the Anjasmoro soybean variety in response to PGPR and nanosilica fertilization. A factorial Completely Randomized Design (CRD) was employed, consisting of nanosilica concentrations (0, 100, and 200 ppm) and PGPR concentrations (0, 5, 10, and 15%). The results indicated that PGPR and nanosilica fertilization improved soybean tolerance to drought stress. The most effective treatment for enhancing the growth and yield of the Anjasmoro soybean variety on Regosol soil was the application of 10% PGPR combined with 200 ppm nanosilica. This treatment significantly increased pod number, pod weight, 100-seed weight, fresh shoot weight, dry shoot weight, fresh root weight, and chlorophyll content. Additionally, the application of 5% PGPR combined with 200 ppm nanosilica resulted in the best seed quality